Satanism, Magic and Mysticism in Fin-de-siècle France - Ziegler, R. author. aut Link
VI, 229 p.
Keywords: An interdisciplinary study of the supernatural and the occult in fin-de-siècle France (1870-1914), the present volume examines the explosion of interest in devil-worship, magic and mysticism both from an historical perspective and through analysis of key literary works of the period.